A decrease in newly diagnosed patients with adult T-cell leukemia/lymphoma in Kagoshima, a highly endemic area of HTLV-1 in southwestern Japan. Issue 4 (21st March 2023) - Owatari, Satsuki; Tokunaga, Masahito; Nakamura, Daisuke; Uozumi, Kimiharu; Sagara, Yasuko; Nakamura, Hitomi; Haraguchi, Koichi; Nakano, Nobuaki; Yoshimitsu, Makoto; Ito, Yoshikiyo; Utsunomiya, Atae; Otsuka, Maki; et al.
Abstract: Adult T-cell leukemia/lymphoma (ATL) is a peripheral T-cell malignancy caused by human T-cell leukemia virus type-I (HTLV-1). This study investigated whether the number of newly diagnosed patients with ATL is decreasing in the background of a declining number of individuals infected by HTLV-1 in Kagoshima, Japan, one of the most endemic areas of HTLV-1 in the world. We retrospectively analyzed the number of newly diagnosed patients with ATL between January 2001 and December 2021 in three major hospitals. The number of newly diagnosed patients with B-cell non-Hodgkin lymphoma (B-NHL) in the same period was examined as an internal control. One thousand eighteen and 2, 029 patients with ATL and B-NHL were registered, respectively. The age-adjusted incidence of ATL steadily increased between 2001 and 2012, whereas that between 2013 and 2021 decreased. Despite the limitation of its retrospective nature, this is the first report indicating a decrease in ATL patients in Japan.